Teodora e Porcina: faces simbólicas da natureza em narrativas de mulheres sábias - Celestino, Luciana Carlos (2011)
This research looks at the collective imagination in which it keeps alive the issue of heroin wise. Two wise women appear in the narratives of popular history and the History of Donzela Theodora and History Imperatriz Porcina, collated by Luís da Câmara Cascudo in his Five Books of the People. The universality, mobility and circularity of these narratives are discussed by authors such as Bakhtin and Guinzburg. The research is developed from three key categories: Knowledge Magic as the knowledge of tradition (Almeida), sensitive knowledge (Levi-Strauss), thought mythical / magical / symbolic (Morin); Wise Women as carriers of this knowledge, which merge and overlap with the imagery of witches and healers; and Mythical Elements which corresponds to the archetypal images (Jung and Silveira), symbols and other images that relate to the magic universe, the magical beliefs and practices considered, ie belonging to the imaginary magic (Bethencourt). Porcina and Theodora are understood as bearers of knowledge of Métis (Detienne and Vernant), or the cunning intelligence, the manipulation of phármakon (Derrida), the healing potion, which may be the word or ointment of the herb. The route takes us to meet the great archetype of the Wise Woman as psychic power of the feminine, the anima. Narratives are medicinal balms (Estes) and is the clash between the anima and its embodiments by wise women, and animus, his opponents, which gives the transmutation of the psyche, a work comparable to that of alchemyThe Knowledge Magic, operating through the female, myth and nature can recover from its essential value to the emerging paradigm that suggests a more complete human science and a more plural